2016
DOI: 10.1002/ird.2023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different operation scenarios on sedimentation in irrigation canals of the Gezira Scheme, Sudan

Abstract: Sediment and water management are key issues in irrigation schemes that suffer from accumulation of sediment along canals. This accumulation creates problems with adequate water supply and may lead to water shortage. The aim of this study was to analyse improvement options for operation and maintenance in order to achieve better sediment and water management in irrigation canals. A model has been developed to simulate cohesive sediment transport in irrigation canals. The model is a useful tool to predict cohes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Reference [17] found in one of her operation scenarios that reduced inflows during the high sedimentation period by 51% led to sediment reduction of 48%. In this paper in our first operation scenario, the same timings and gate settings were used as used by Reference [1] but kept the flow and (high) sediment concentration constant.…”
Section: Discussionmentioning
confidence: 99%
“…Reference [17] found in one of her operation scenarios that reduced inflows during the high sedimentation period by 51% led to sediment reduction of 48%. In this paper in our first operation scenario, the same timings and gate settings were used as used by Reference [1] but kept the flow and (high) sediment concentration constant.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies regarding cohesive sediment behavior have been done in rivers and estuaries [10][11][12][13][14][15]. There is a great need to study the mechanism of cohesive sediment transport in irrigation canals [16], in particular under different scenarios of gate operation.The impact of gate operation on the cohesive sediment in the Gezira Scheme in Sudan has been studied by Reference [17]. They considered two gate operation scenarios: (1) a system in which water allocation is based on water duty and the cropped area and water is given by a fixed discharge for one week.…”
mentioning
confidence: 99%
“…They found that the latter scenario performs best, reducing sediment deposition to 48%, primarily because the intake of the amount of sediment-laden water is reduced. References [9,17] both used a 1D model while the behavior of cohesive sediments is best reflected in 2D/3D models [18].The main objective of this paper is to investigate the role of gate operation in reducing the amount of cohesive and non-cohesive sediment in the canals using a 2D/3D model. This paper builds on the work by Reference [1] on the sediment deposition patterns in the Gezira irrigation scheme and uses the baseline data collected by her.…”
mentioning
confidence: 99%
See 2 more Smart Citations